Influence of Mg and Ti substitutions on structural, microstructural, characteristics of Ni-Zn ferrites - Lee, Sok Yen; Rodziah, Nazlan; Idza Riati, Ibrahim; Bahmanrokh, Ghazaleh (EDP Sciences, 2025)
Ni-Zn ferrites (NZF) are technologically important soft magnetic materials, and their performance can be tuned by selective cation substitution. In this study, Mg- and Ti-doped NZF with compositions Ni0.3Zn0.7-xMgxFe2O4 and Ni0.3Zn0.7-xMgxFe2O4 (x=0.000–0.075) were synthesized via the oxide-mixture route to investigate the influence of dopants on structural, microstructural, and magnetic properties. XRD analysis confirmed the formation of a single-phase cubic spinel structure for all samples. Lattice parameter analysis revealed moderate contraction with Mg doping and more pronounced distortion with Ti-doping, indicating distinct cation effects on the crystal structure. SEM observations showed that Mg doping promoted densification and grain growth, resulting in a well defined microstructure with reduced porosity. In contrast, Ti-doping suppressed grain growth and produced finer grains with higher porosity. Magnetic measurement revealed contrasting behaviours where Mg doping enhanced Ms from 77.50 emu/g in undoped NZF to 84.58 emu/g at x=0.075, attributed to improved domain wall mobility and superexchange interactions. Conversely, Ti doping reduces Ms to 65.84 emu/g at x=0.075 due to lattice distortion, valence change imbalance, and grain boundary pinning. These findings reveal that Mg acts as a magnetic enhancer and sintering aid, whereas Ti disrupts the magnetic ordering, proving new approaches for tailoring NZF performance for advanced applications.